Transformasi Nilai Integritas Melalui Pendidikan Anti Korupsi Berbasis Masyarakat Sekolah Dalam Membangun Ketahanan Sosial - Nadia Raisa Nukma; Wisnu Pangestu; Wahyu Tri Lestari; Nur Asih Triatmaja (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2025)
Corruption is a major problem that continues to hamper Indonesia's progress, marked by the high level of corrupt practices involving various levels of public officials and educational institutions. This condition emphasizes the importance of early anti-corruption education to shape the character of an integrated young generation. The Anti-Corruption Education socialization activity at MA AL IHSAN Doglo was carried out as an effort to empower the school community in strengthening the values ​​of integrity and social resilience against corrupt practices. The activity was carried out offline on December 5, 2025, involving 70 students from grades 10, 11, and 12. The methods used included material delivery, questions and answers, ice briking, observation, and documentation, thus allowing for direct interaction between the presenters and students. The material presented covered forms of corruption relevant to the school environment, such as stone corruption, corruption of abuse of office, and administrative corruption. The results of this activity showed increased enthusiasm and participation of students, as well as an increased understanding of the concept and prevention of corruption based on evaluations before and after the socialization. Thus, this activity is considered effective in fostering an anti-corruption attitude and is expected to encourage students to become agents of change who can pass on the values ​​of integrity in the community. This activity contributes to strengthening character education and building social resilience through school-based anti-corruption education. This activity also aims to establish a school culture free from dishonest practices, encourage students' courage in rejecting and reporting corrupt behavior, and strengthen the role of teachers and schools as role models in preventing corruption. Through this socialization, it is hoped that students will develop critical awareness and a commitment to becoming a generation of integrity capable of preventing corruption from an early age.